P240 SHORT–TERM EFFECT OF SGLT2I ON ECHOCARDIOGRAPHIC PARAMETERS IN HFREF PATIENTS TREATED WITH ARNI. (18th May 2022) - Mazzetti, S; Cannistraci, R; Scifo, C; Acone, L; Alonge, S; Foti, M; Tarantini, R; Lattuada, G; Perseghin, G; Mortara, A
Abstract: Background: Treatment with Sacubitril / Valsartan (ARNI) in patients with heart failure and reduced ejection fraction (HFrEF) promotes significant improvement of left ventricular remodeling along with positive outcomes in terms of hospitalization for heart failure, quality of life and mortality. In a previous study we demonstrated that ARNI significantly modifies myocardial longitudinal strain (GLS), one of the most reliable markers of myocardial contractility. It is still debated whether this effect remains unchanged regardless of the presence of diabetes and if it can be further increased by SGLT2 inhibitors, which in turn have been shown to reduce hospitalizations for heart failure and cardiovascular mortality. Purpose: of this ongoing study is to measure, in HFrEF patients with or without T2DM, treated with ARNI and SGLT2i, short–term changes (6 months follow up) of the main echocardiographic parameters, including GLS Methods We enrolled 40 outpatients (32 male, age 65 + 10 years, EF 29, 7 + 6, 5%) on optimized medical treatment with class I medications, including ARNI at the maximum tolerated dose (starting dose 75 + 15mg, maximum titrated dose 190 + 10mg). Population was then divided into three groups: group 1 (20 pts) without T2DM; group 2 (11 pts) with T2DMI; group 3 (9 pts) with T2DM on SGLT2i treatment (4 with empaglifozin 10 mg, 5 with dapaglifozin 10 mg). No hemodynamic or metabolic complications related with therapy were observed, and no patients needed discontinuation or down–titration of therapy All patient underwent echocardiographic study at baseline and after six–month follow–up. Conclusions: This ongoing study confirms that, in HFrEF patients, ARNI positively modifies left ventricular contraction and remodeling, and this effect is still verified regardless of the presence of T2DM. The association with SGLT2i, conversely, does not appear to provide further positive benefits on remodeling.